2011
DOI: 10.1002/cbdv.201000331
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Antileishmanial Activity and Toxicity of Essential Oils of Artemisia absinthium and Echinops kebericho

Abstract: Potential toxicity, costs, and drug-resistant pathogens necessitate the development of new antileishmanial agents. Medicinal and aromatic plants constitute a major source of natural organic compounds. In this study, essential oils of Artemisia absinthium L. and Echinops kebericho Mesfin were investigated by GC and GC/MS analyses. Isolated oils were screened for antileishmanial activity against two Leishmania strains (L. aethiopica and L. donovani), and toxicity on the human monocytic leukemia (THP-1) cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 45 publications
4
69
0
1
Order By: Relevance
“…Antileishmanial activity was also reported against promastigote and axenic amastigote stages of Leshmania aethiopica and L. donovani (Tariku et al, 2011). Phytochemical analysis of root extracts of the plant also showed the presence of many antimicrobial chemical compounds (Ashebir and Ashenafi, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…Antileishmanial activity was also reported against promastigote and axenic amastigote stages of Leshmania aethiopica and L. donovani (Tariku et al, 2011). Phytochemical analysis of root extracts of the plant also showed the presence of many antimicrobial chemical compounds (Ashebir and Ashenafi, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…The latter report found IC 50 values ranged from 0.21 to 0.58 mg/ml for Absinthium indica, while another report on A. absinthium against L. major demonstrated an IC 50 value of 0.28 mg/ml (Kheiri Manjili et al 2012). Essential oils from A. absinthium demonstrated growth inhibitory effects at certain concentrations against promastigotes of two different Leishmania species (Tariku et al 2011). Similarly, the growth inhibitory activities of 11 different Artemisia species were shown against the promastigotes of L. major (Emami et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…About 400 species are described globally of which some 30 species are present in Iran only two of which are native to this country. They are known to have diverse antiparasitic (Rocha et al 2005;Sen et al 2007;Abdel-Sattar et al 2010), antibacterial (Ramezani et al 2004;Valdes et al 2008;Ahameethunisa and Hopper 2010), antifungal (Kordali et al 2005), antioxidant and antidepressant (Mahmoudi et al 2009;Ali et al 2013) and cytotoxic (Tariku et al 2011) effects. Their efficacy could be due to the presence of an endoperoxide bridge at the heart of artemisinin, a bitter substance derived from extracts of wormwood (Krishna et al 2008).…”
mentioning
confidence: 99%
“…The study showed reduction in ulcer index, increase in level of mucin, reduction in peptic activity and decrease in gastric juice volume [42]. [44]. Wormwood also exhibited antiprotozoal activity against Leishmania donovani, Leishmania infantum, Plasmodium falciparum and Trypanosoma cruzi [45].…”
Section: Antiulcer Activitymentioning
confidence: 99%